Case report: Therapeutic drug monitoring and CYP2D6 phenoconversion in a protracted paroxetine intoxication - Damborská, Alena; Hanáková, Lenka; Pindurová, Eva; Horská, Kateřina (Frontiers in Pharmacology, 2024)
Objective The cytochrome P450 2D6 (CYP2D6) is an enzyme involved in the oxidative biotransformation of various widely used drugs, including paroxetine, a substrate and strong inhibitor of the enzyme. The aim is to report on a case of protracted intoxication with paroxetine after a single overdose in a genotype-predicted intermediate CYP2D6 metabolizer. Observation A 49-year-old man was receiving chronic treatment for more than 6 years with paroxetine 60 mg/day for an indication of agoraphobia. The patient ingested fifty 20 mg tablets of paroxetine in a suicide attempt. The toxic plasma level, accompanied by delirium, persisted for approximately 1 month after the overdose. According to the genotype profile, the patient was evaluated as an intermediate metabolizer with reduced CYP2D6 enzyme activity. Conclusion As a consequence of the suicide attempt with overdose and the chronic paroxetine treatment that preceded it, phenoconversion to a poor metabolizer with very low CYP2D6 enzyme activity is suggested as contributing to an extremely long intoxication accompanied by delirium. Prolonged monitoring over a standard 24 h of both physical symptoms and drug plasma levels, together with a genetic profile assessment and phenoconversion consideration, is recommended after a single overdose in patients chronically treated with paroxetine.